Current Problems of International Legal Migration Safety Promotion in Russia - E. V. Tarasyants (Московский журнал международного права, 2011)
This article contains information on the conference “Current problems of international legal migration safety promotion in Russia” which is regularly organized by the Academy of Economic Security of the Ministry of Internal Affairs of Russia. Specialists in various fields of migration participate in the conference and discuss the most acute migration problems.